Development and Application of Smart Packaging Solutions for Extending the Shelf Life of Fresh Produce - Mohamed Al Hassan; AI_Sadi Hafidh l.; Hemalatha K. (SHS Web of Conferences, 2025)
Smart packaging plays a vital role in enhancing food safety and quality by enabling real-time monitoring and control of environmental conditions. This technology ensures that food is stored under optimal conditions, effectively preventing spoilage, extending shelf life, and reducing waste, thereby improving consumer satisfaction. The implemented smart packaging system involves several integrated stages. First, the packaging design incorporates sensors and indicators seamlessly, ensuring both functionality and structural integrity. Temperature sensors (RTDs), humidity sensors, and gas detectors are embedded within the packaging layers to continuously monitor conditions. Color-changing freshness indicators are strategically placed to provide real-time visual feedback: green indicates optimal freshness, yellow signals approaching expiration, and red warns of compromised quality. QR codes offer consumers detailed product information and traceability. The sensors relay data to the freshness indicators, ensuring accurate and timely updates on food quality. This system empowers consumers to make informed purchasing decisions, reduces food waste, and enhances food safety and quality throughout the supply chain. The results demonstrate that smart packaging significantly extends the shelf life of food, with improvements of up to 99.99% compared to traditional methods. Gas sensors effectively preserve food quality, as shown by strong correlations in scatter plots. Real-time monitoring of temperature and humidity prevents spoilage, while visual freshness indicators provide clear, intuitive alerts, promoting better consumer management and reducing waste. Overall, the smart packaging system offers substantial benefits by maintaining food integrity and boosting customer satisfaction.